The Association of HOTAIR with the Diagnosis and Prognosis of Gastric Cancer and Its Effect on the Proliferation of Gastric Cancer Cells - Zhiying Xu; Hui Chen; Bin Yang; Xiangfeng Liu; Xiaoli Zhou; Hongfang Kong (Canadian Journal of Gastroenterology and Hepatology)
Background. Long noncoding RNAs (lncRNAs) are a group of noncoding RNA with the length of more than 200nt. They have been identified as important diagnostic and prognostic molecules for many cancers and play an important role in the development of cancers. However, their clinical value and roles in gastric cancer (GC) remain unclear. Methods. The expression levels of HOTAIR in 54 GC tissues and their matched adjacent nontumor tissues from GC patients and 24 normal mucosa or those with minimal gastritis as healthy controls were determined by qRT-PCR. The expression levels of HOTAIR in human GC cell lines and a normal gastric epithelium cell line were also assessed by qRT-PCR. The potential relationships between its level in GC tissues and the clinicopathological features were analyzed. Furthermore, a receiver operating characteristic (ROC) curve was constructed. Additionally, the correlation between this lncRNA and overall survival (OS) was analyzed. SiRNA transfection was used to silence the expression of HOTAIR in GC cells. And cell proliferation and cell cycle assays were employed to determine the effect of HOTAIR on GC cell growth. Western blot was performed for the detection of the P53, P21, and Bcl2 proteins. Results. The expression levels of HOTAIR were significantly upregulated in GC tissues and cell lines. Increased HOTAIR was associated with tumor differentiation, lymph node and distant metastasis, and clinical stage. Furthermore, the area under the ROC curve (AUC) was up to 0.8416 (95 % CI=0.7661 to 0.9170, P<0.0001). The sensitivity and specificity were 66.67 and 87.04%, respectively. The correlation between HOTAIR expression and overall survival (OS) was statistically significant. The hazard ratio was 2.681, and 95% CI of ratio was 1.370 to 5.248. In addition, knockdown of HOTAIR can inhibit GC cell growth and affect cell cycle distribution. And knockdown of HOTAIR could enhance the protein levels of P21 and P53. Conclusion. The present study demonstrated that HOTAIR was highly expressed in GC tissues and may serve as a potential diagnostic and prognostic biomarker for GC. And HOTAIR promoted GC cell proliferation.